A study on the Role of Multilingualism in Enhancing Communication Skills Among University Students in India (International Journal of Food and Nutritional Sciences, 2019)
Multilingualism in India is a dynamic and complex linguistic phenomenon lying beyond simple language ability. This research focuses on how the cognitive, social, and pedagogical aspects of multilingualism can be used to enhance the communication skills of the university students. Through an investigation of how linguistic variety has become a sophisticated communication instrument amidst India’s extraordinary linguistic landscape comprised of at least 122 recognisable languages belonging to 1,599 different tongues, the study analyses the complex intertwining between the two realms. Research demonstrating multilingualism as complex cognitive and social practice is achieved by the use of interdisciplinary theoretical frameworks like the language repertoire model, sociocultural linguistic methods, and cognitive advantage theory. It was found that those who are multilingual are ahead in cognitive control, comes with higher functioning in executive function and are more skilled communicators than those who are monolingual. The research also analyzes finely the intricate link between language variety and communication skill, and explores student strategy for travelling across, if not many, then several language codes. Multilingualism is rich ground in key discoveries of the cognitive benefits of being multilingual, including more cerebral flexibility, better problem solving, and communication adaptability. Additionally, the study reveals the multilingual communication in its multi facet sociocultural aspects where language becomes a salient sign not only of social interaction, but at the same time of culture identity. This research investigates the possibilities and problems of language variety, and provides a detailed overview of the potential of multilingualism as a cognitive and social resource in cultural contexts.